2003
DOI: 10.1093/bioinformatics/btg209
|View full text |Cite
|
Sign up to set email alerts
|

Diametrical clustering for identifying anti-correlated gene clusters

Abstract: We present a new diametrical clustering algorithm that explicitly identifies anti-correlated clusters of genes. Our algorithm proceeds by iteratively (i). re-partitioning the genes and (ii). computing the dominant singular vector of each gene cluster; each singular vector serving as the prototype of a 'diametric' cluster. We empirically show the effectiveness of the algorithm in identifying diametrical or anti-correlated clusters. Testing the algorithm on yeast cell cycle data, fibroblast gene expression data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 28 publications
1
66
0
2
Order By: Relevance
“…Another possible explanation is that the subunit II genes in the six species were analogously displaced by unrelated sequences (nonorthologous replacement). Indeed, displacement of an enzyme is now widely acknowledged as an important source of phylogenetic difference (Dhillon et al 2003;Morett et al 2003). All subunit II genes from the Staphylococcus-Bacillus cluster were used as query sequences to find potential homologues without regard to the physical location relative to subunit I.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that the subunit II genes in the six species were analogously displaced by unrelated sequences (nonorthologous replacement). Indeed, displacement of an enzyme is now widely acknowledged as an important source of phylogenetic difference (Dhillon et al 2003;Morett et al 2003). All subunit II genes from the Staphylococcus-Bacillus cluster were used as query sequences to find potential homologues without regard to the physical location relative to subunit I.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-correlation has been observed to imply functional similarity of genes [9]; we plan to extend our co-clustering algorithms to detect such anti-correlations.…”
Section: Discussionmentioning
confidence: 99%
“…For a survey, see [12]. Dhillon et al [9] present diametric clustering for identifying anti-correlated gene clusters for it is observed that genes that are functionally related may demonstrate strong anti-correlation in their expression levels. All of the above work is focussed on clustering genes using conditions as features.…”
Section: Introductionmentioning
confidence: 99%
“…We also assume a constant and positive concentration parameter κ > 0. The associated Bregman divergence D W is then a scaled cosine-squared dissimilarity measure, which is equivalent to the measure used for diametrical clustering-the asymptotic limit of a mixture of Watsons [4,12]. The Bregman divergences for the Gaussian and Watson distributions can then be used to define hard clustering algorithms, which we'll describe next.…”
Section: Gaussian and Watson Distributionsmentioning
confidence: 99%